(untitled) (Journal of the College of Basic Education, 2022)
This research aims at identifying. The Effect of Distinctive and Pluralistic Teaching Strategies on Fifth Primary Female Students Achievement in Kurdish Grammar. The researcher has followed the experimental way of research because it suits the nature of the research. The research sample consists of (69) female students distributed (23) female students according to Distinctive Teaching Strategy. Als )23( female Students represents the second experimental group which is taught according to pluralistic Teaching Strategy .The control group includes(23) female students which is taught according to the traditional way of teaching. The three group are matched in terms of three variables : the students age (in months)، their parent’s academic level of education، their intelligence. The researcher has constructed a multiply item test which includes (30) items. The reliability of the test has been ascertained by using Alph – cronpach Method and it is (0.83) The results show that both strategies are effective. The researcher has come up with a number of suggestion’s and recommendations which all have educational value.